Fraud in the comperative perspective of civil and criminal law with special focus in Kosovo - Hajdari, Egzonis; Hajdari, Albulena; Hajdari, Azem (Brawijaya Law Journal : Journal of Legal Studies, 2021)
The object of this study is fraud in the comparative aspect of civil and criminal law based on the relevant legislation and Kosovo legal theory. The results of this study prove that fraud in the Kosovo courts practice is relatively common, and that there are many irregularities in its handling. Irregularities mostly refer to the lack of clarity matter of differences that this harmful phenomenon contains in itself when handled in the civil legal aspect from the treatment given to it in the criminal legal aspect. These uncertainties have influenced that in each concrete case the phenomenon of fraud in Kosovo is first addressed in the criminal aspect and then eventually in the civil aspect. The study highlights the similarities, differences and existing ambiguities of fraud when handled in the civil legal aspect from the treatment given to it in the criminal legal context, as well as it addresses the appropriate ways of clarifying such situation. The contribution of this study is theoretical and practical, bearing in mind the fact that it deals with an almost unaddressed issue in Kosovo and perhaps in many other countries.